2019
DOI: 10.1016/s2214-109x(19)30315-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-line drinking water chlorination at the point of collection on child diarrhoea in urban Bangladesh: a double-blind, cluster-randomised controlled trial

Abstract: Background Previous blinded trials of household water treatment interventions in low-income settings have failed to detect a reduction in child diarrhoea. Technological advances have enabled the development of automated in-line chlorine dosers that can disinfect drinking water without electricity, while also allowing users to continue their typical water collection practices. We aimed to evaluate the effect of installing novel passive chlorination devices at shared water points on child diarrhoea prevalence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 35 publications
5
133
1
Order By: Relevance
“…This analysis was nested within a previously described, cluster-randomised controlled trial of a point-of-collection chlorinator on self-reported diarrhoea in children in two urban and peri-urban communities in and around Dhaka, Bangladesh (NCT02606981) [23]. While this analysis is cross-sectional for the specified outcomes in children in both intervention and control groups, the parent trial included data collection from an open cohort of children <5 years old (enrolled for a baseline (pre-intervention) evaluation between July and November 2015, and followed-up approximately every 2 months over seven post-intervention rounds (rounds 1–7) from November 2015 to December 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis was nested within a previously described, cluster-randomised controlled trial of a point-of-collection chlorinator on self-reported diarrhoea in children in two urban and peri-urban communities in and around Dhaka, Bangladesh (NCT02606981) [23]. While this analysis is cross-sectional for the specified outcomes in children in both intervention and control groups, the parent trial included data collection from an open cohort of children <5 years old (enrolled for a baseline (pre-intervention) evaluation between July and November 2015, and followed-up approximately every 2 months over seven post-intervention rounds (rounds 1–7) from November 2015 to December 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Follow-up was discontinued if the child aged out of the cohort or had migrated out of the study area and could no longer be located. The study protocol was approved by the scientific and ethical review boards of the International Centre for Diarrheal Disease Research, Bangladesh (icddr,b, protocol 14022) and the human subjects institutional review board of the Stanford University (protocol 30456) [23]. CDC coauthors (Berendes) received de-identified data for analysis as per a non-disclosure agreement with the Principal Investigator (Pickering).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved water quality and safely managed waste could indirectly decrease antibiotic use (Figure 2), yet few studies have investigated this association 84 . We suggest that Objective measurements are preferred since residents may not recall the types of antibiotics they have recently consumed or the frequency with which they have consumed them when self-reporting .…”
Section: ) Quantify the Impacts Of Improved Water Quality And Safelymentioning
confidence: 99%
“…They tested the effect of a device (Aquatabs Flo, Medentech, Inc., Wexford Ireland), which automatically chlorinates piped water, on child diarrhoea. 9 As is common in low-income settings, the municipal piped water in the study area was delivered only intermittently; this limitation causes sporadic pressure drops in the piped networks which hydraulically facilitates entry of microorganisms into the pipe lumen through backflow or cracks. 10 The device was fitted at the inlet of large water storage tanks fed by municipal piped water; the device did not require electricity and produced water with a sufficient chlorine residual to continue disinfecting water after collection if it was re-contaminated by dirty storage containers, utensils, or hands.…”
Section: Reducing the User Burden In Wash Interventions For Low-incommentioning
confidence: 99%